Adult intussusception – a rare cause of intestinal obstruction in adults - Poškus, Tomas; Grišin, Edvard (Lietuvos chirurgija, 2015)
Background Intestinal intussusception is a rare cause of abdominal pain in adults and stands for only 5% of all cases with acute abdominal pain. While the clinical signs of pediatric invagination are obvious, surgeons struggle with preoperative diagnosis of adult intestinal invagination because of non-specific symptoms, which can result in misleading diagnosis. Therefore, it is mandatory to evaluate the risk of bowel intussusception when there is lack of evidence to explain constipation symptoms in adults. Methods The correct diagnosis of bowel obstruction can lead to tumor detection, which causes 86% of small bowel intussusception in adults. Ultrasound and plain X-ray examination procedures are not effective to diagnose intestinal obstruction. CT is the “golden standard” diagnostic procedure; therefore, it is mandatory for doctors to correctly interpret the non-specific obstruction (“target” or “sausage shaped” thickened part of a bowel) signs. Results The abdominal ultrasound showed minimal fluid in the right iliac fossa where appendectomy was performed a week ago. The plain X-ray examination of the abdomen did not show signs of small bowel obstruction. The CT scan performed later on showed ileocecal intussusception, dilated bowel loops and signs of regional lymphadenopathy, which was the main indication for immediate surgery. Conclusion Intestinal intussusception is a rare cause of adult recurrent abdominal pain, which can be misled by an insufficient diagnostic criteria. The CT imaging is the most precise diagnostic method in early pathology detection. Resection of involved bowel is recommended when treating these patients because, in most cases, intussusception is caused by a neoplasm of the bowel.